POLA PENGGUNAAN TELEPON SELULER (PONSEL) OLEH SISWA DI SMA NEGERI 2 BAYANG KABUPATEN PESISIR SELATAN - Widuri, Dela; Prahara, Surya; Rahmad, Darmairal (Pendidikan Sosiologi, 2014)
The use of handphone by students in the school performed continuously or repeatedly regardless of place and time. Students using handphone while walking, while eating, hanging out with friends, waiting for public transport, to the toilet, and certain places in school and the mobile phone is not only used for communication but for internet browsing and so on and it is interesting to study how patterns of handphone use by student at SMAN 2 the Bayang. This research was conducted using a qualitative approach and descriptive type. Selection of informants of this study conducted by purposive sampling, the study informants numbered 22 people, 2 teachers and 20 students. The data of this study is primary data and secondary data. Primary data is data obtained from all study informants, and secondary data is all the data obtained from such schools as supporting documents rule, the data of teachers and students, and remarks offens. Data collection techniques in this study is the use of interview techniques, observation and documentary. All data obtained were processed and analyzed using triangulation techniques through several phases; stage of data collection, data reduction, data display and conclusion drawing process. From the results of this study revealed that there are four patterns of handphone use by students at SMAN 2 Bayang, ( 1 ) the pattern of handphone use by students is based on the time that there is a pattern that is going in 10 hours of lessons ( morning ) for the purposes of study , business , fun, and for emergency purposes . In the class for fraudulent purposes . During a break in business and at home for fun and for business , for fun and for emergency purposes . ( 2 ) the pattern of handphone use by students is based on the person contacted that there are 7 patterns to contact the teacher for the purposes of the studi, call a friend to kepeluan study, call a friend for business, call a friend for fun, contact parents for emergency purposes , to contact a girlfriend for fraudulent purposes , and to contact strangers for fraudulent purposes . ( 3 ) the pattern of handphone use by students based on where there is a pattern that is in class 9 for the purposes of study, fun, and emergency. In the literature for the purposes of the studi, in the parking lot for fun, in the park for fun, in certain places for business, for fun and emergency purposes . and ( 4 ) the pattern of handphone use by students based on frequently used applications , there are 8 pattern is a game application for fraudulent purposes , facebook for business and for fun , google for the purposes of the study , for fun and for emergency purposes , MP3 for fraudulent purposes and the use of the camera for the purposes of fad . Keywords : pattern , handphone usage , students